Membentuk karakter unggul melalui pembelajaran Pendidikan Kewarganegaraan - Lestari, Dwi Indah; Kurnia, Heri; Fatmawati, Fifi; Fauziah, Resvi Septiani (Jurnal Pendidikan Kewarganegaraan dan Politik, 2024)
Civic Education (PPKn) plays a crucial role in shaping individuals' characters and fostering positive behaviors. This article discusses the challenges and opportunities in optimizing the role of PPKn. The introduction emphasizes the importance of civic values in social life, while the method discusses effective teaching strategies, including active approaches, the use of technology, integration of civic values into other subjects, and collaboration among relevant parties. The discussion highlights challenges such as lack of awareness of the importance of PPKn, disparities in curriculum implementation, and complexity of the material, while opportunities such as technological advancements, collaboration, and periodic evaluations provide a foundation for enhancing the effectiveness of PPKn education. By utilizing appropriate strategies and involving all relevant stakeholders, it is hoped that a future generation with strong character, responsibility, and civic awareness can be realized.